Brilliance in Europe - Han, Sanping 1953-; Yan, Xiaoming; Zhou, Wei 1954- ([China] : Confucius Institute, Movie and TV Resources for Chinese Language Learning, 2007)
Presenta la lucha de una fábrica de iluminación china por ingresar al mercado europeo
Screenwriter Wang Qiang ; director of photography, Sun Yeping ; editor, Li Tingzhan
Elenco: Liu Changchun, Li Fengxu, Zeng Qlusheng, Zhang Yongxlang
En chino con subtítulos en chino e inglés
Keywords: CINE CHINO; PELICULAS CINEMATOGRAFICAS -- CHINA